Mapping Personality to Enhance Personal Effectiveness - Sharma, Ekta (Prabandhan: Indian Journal of Management, 2015)
The curiosity to know what makes people effective and competent in their personal behaviour is as old as mankind. Many psychologists, sociologists, and spiritual leaders are in the quest of the answer to : what is the good life ? Personal effectiveness is considered a way to good life as it is a catalyst in developing oneself. It has been observed that personal effectiveness improves the life satisfaction index and also the productivity of an individual. If a counselor or mentor studies the personality of his/her subject, he/she would be able to pave the way to personal effectiveness of the subject. The current research intended to find out the personality traits that influenced the personal effectiveness levels of the respondents. The sample of the study was 112 subjects between the age group of 22 - 50 years. The study showed a significant relationship between personal effectiveness and personality factors.